HUBUNGAN ANTARA ORIENTASI RELIGIUS DENGAN KONTROL DIRI DALAM PERILAKU SEKS PRANIKAH PADA REMAJA YANG BERPACARAN - Jeny Citra Sari Ajan; Flora Grace Putrianti (JURNAL SPIRITS, 2012)
ABSTRACTThis research is to find out the relationship between religious orientation with the self-control in pra-wedding sex behaviour among the adolescent who has engage. The subjects of this research is taken 105 students of Psycology in Sarjanawiyata Tamansiswa University, Yogyakarta.Data was collected by interview, observation, and testing method. The research insruments are the scale of self-control in pra-wedding sex and the scale of religious orientation, Data analysis by the correlation product moment and independent sample test.According to the result of the data is r = 0,587 with the level of the significant is p = 0,000 (p<0,05). The effective contribution of the religious orientation to the self-control in pra-wedding sex behaviour is r2 = 34,4%. This result shows that 65,6% of the self-control can be determined by another factors, such as the age, family environment, situation, etnic, and experiences.The conclusion of this research is that there is a positive relationship between religious orientation to the self-control in pra-wedding sex behaviour among the students.Key words: religious orientation, self-control, pra-wedding sex.